Gong dan Mantra sebagai Simbol Komunikasi bagi Masyarakat Dayak Kalimantan Barat - Zakarias Aria Widyatama Putra; Yudhistira Oscar Olendo; Christanto Syam; Mastri Dihita Sagala (Ideas Publishing, 2023)
Modern era directs the younger generation of Dayak people in West Kalimantan towards cultural identity, especially gongs and mantras in meaning and function.. The purpose of this research is to identify the role of gongs and mantras as symbols of cultural communication. Through a qualitative method with the type of Roland Barthes semiotics, it is a way to reveal research on the role of gongs and mantras which is also accompanied by Susanne Knauth Langer's communication symbol theory. The gong as an accompaniment to the wood products and the mantra as a request imply a communication message between humans and God in the Nyobeng ritual of the Dayak Bidayuh community. The communication message implies the good side for the welfare of the Dayak community.